The effect of load carriage among primary school boys: a preliminary study - Shasmin, H.N. (2007)
Backpack carrying is a considerable daily " occupational" load among schoolchildren. Most of the research on children's backpacks have focused on gait pattern and trunk forward lean; only a few researches have investigated the impact of backpack carrying on children using the measurements of static posture and gait kinetics. This study investigated the changes in ground reaction force (GRF) and trunk inclination among primary students when carrying heavy backpacks. A randomized controlled experimental study was conducted on seven boys aged between 9 and 11 years old with a similar body mass index. Observations were done when the boys were carrying school bags of 0 ( as control), 10, 15, and 20 of their own body weight while walking normally. Data acquisition was carried out using force platforms and a 3D motion analysis system. A significant difference in GRF at a load of 20 of body weight was found: the vertical GRF increased almost three times when loads increased up to 20 of body weight compared to 10 of body weight. The anterior-posterior GRFs were asymmetrical when loads were increased. When carrying a load of 15 of body weight, all of the seven subjects adopted a compensatory trunk inclination. The emphasis on GRF and trunk inclination suggests that the safest load applied does not exceed 15 of body weight.